A criação do inquérito policial: Estado e polícia no Espírito Santo - Almeida, Paulo Vinicius de (2007)
To present Dissertation it discusses the institution of the Brazilian Police when, the century in the century XIX, had won outlines in response to the social dynamics of the moment of the formation of the State-nation. In synthesis, the criminal procedure, disciplined in the Code of the Criminal Process of 1832 passed for incidental reforms with the Law 261 of December 3, 1841, that it had provoked an emptying of the functions jurisdicionais of Paz's Judges, and it transferred those functions for the authorities police and magistrates. The delegation In what it concerns to the safety interns, in Espírito Santo Provincia, as in the others, that function had been under the responsibility of the military bodies of patents, only appearing in lands capixaba a Corpo Policial in definitive and gone back to the maintenance of the social order, in 1856, even so with a contingent on this side of the necessary. In compensation, the Body of Police possessed an inverse logic to the criminality index, at the same time in that he/she was devoted the contention of the disorders much more, and do not criminal processes that in the great majority. In terms of applicability of the justice, with the study of Criminal Solemnities cultivated in Victoria's District among 1865 to 1875, the attempts are confirmed of implanting the General Government's legislations advindas, in spite of the difficulty of filling out the positions of magistracies with individuals of the population. Like this, the documental body formed by the Solemnities made possible to extract the applicability so much of the Law of Reform of 1841, with the reading of processes from 1865 to 1871; as of the Law of the Alteration of the Dispositions of the Judiciary Legislation of 1871, convergent to the processes interposed among 1872 to 1875.